Restoration of quality of life in elderly with hearing loss - Mustafa, Mohamed Wael Mohamed; Abdelrahim, Ahmed Gaber; Khodary, Maha Mahmoud; Aref, Zaki Farouk (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: This study is looking at the daily life consequences of hearing loss in older adults, and how hearing aids (HA) can affect their lives. Method: Everyone who took part in the study had their hearing checked using basic tests. The McCarty Alpiner scale is a way to measure how much personal affection someone has. The Arabic international outcome inventory for hearing aids was used to measure the benefits of using hearing aids. Results: There was a moderate correlation between hearing measurements without hearing aids and psychological, social, and vocational affection. The hearing aid improves your ability to hear, and the better your hearing gets, the higher your hearing threshold will be. However, there is no correlation between age and gender, and this is mainly due to differences in how hearing is processed in males and females. The improvement in the audiological profile of the patient suggests that their personal outcome will be better. Conclusions: Daily life consequences of hearing loss and general life Satisfaction are closely related. Hearing aid is a beneficial rehabilitation method for presbycusis.